Utilisation of complementary and alternative medicine (CAM) practitioners within maternity care provision: results from a nationally representative cohort study of 1,835 pregnant women - Steel Amie; Adams Jon; Sibbritt David; Broom Alex; Gallois Cindy; Frawley Jane (BMC, 2012)
Abstract Background There is little known about women's concurrent use of conventional and complementary health care during pregnancy, particularly consultation patterns with complementary and alternative medicine (CAM). This study examines health service utilisation among pregnant women including consultations with obstetricians, midwives, general practitioners (GPs) and CAM practitioners. Methods A sub-study of pregnant women (n=2445) was undertaken from the nationally-representative Australian Longitudinal Study on Women's Health (ALSWH). Women's consultations with conventional practitioners (obstetricians, GPs and midwives) and CAM practitioners for pregnancy-related health conditions were analysed. The analysis included Pearson chi-square tests to compare categorical variables. Results The survey was completed by 1835 women (response rate = 79.2%). A substantial number (49.4%) of respondents consulted with a CAM practitioner for pregnancy-related health conditions. Many participants consulted only with a CAM practitioner for assistance with certain conditions such as neck pain (74.6%) and sciatica (40.4%). Meanwhile, women consulted both CAM practitioners and conventional maternity health professionals (obstetricians, midwives and GPs) for back pain (61.8%) and gestational diabetes (22.2%). Women visiting a general practitioner (GP) 3-4 times for pregnancy care were more likely to consult with acupuncturists compared with those consulting a GP less often (p=<0.001, x2=20.5). Women who had more frequent visits to a midwife were more likely to have consulted with an acupuncturist (p=<0.001, x2=18.9) or a doula (p=<0.001, x2=23.2) than those visiting midwives less frequently for their pregnancy care. Conclusions The results emphasise the necessity for a considered and collaborative approach to interactions between pregnant women, conventional maternity health providers and CAM practitioners to accommodate appropriate information transferral and co-ordinated maternity care. The absence of sufficient clinical evidence regarding many commonly used CAM practices during pregnancy also requires urgent attention.